G462(P) Anaphylaxis nice guidelines: are we following the guidelines or is there is still a need to improve adherence. (May 2019) - Petrides, C; Doherty, S; Patel, N
Abstract : Aim: NICE has issued guidelines on anaphylaxis management in 2011. Our team tried to investigate whether the paediatric staff in the Emergency Department has been following the NICE guidelines in regards to the assessment, management and referral process of children treated for anaphylaxis. Methods: 23 children up to the age of 16 years old were identified over a 12 month period. Their clinical notes were reviewed to assess the presence of the key criteria of the guideline. The Anaphylaxis NICE data collection tool was used. Data was then analysed and compared to the Trust's standards to assess level of compliance. Results: Good compliance (>95%) was demonstrated in the following: documentation of acute symptoms; admitting patients for observation; referring patients to an allergy service; offering appropriate adrenaline autoinjector to take home. There was acceptable compliance (75%–94%) in documenting the circumstances prior to the onset of symptoms. There was poor compliance (<74%) in the following: recording the time of onset of anaphylactic reaction; information provision to patients and parents on anaphylaxis follow-up and self-management. Conclusion: In general, there is adherence to the anaphylaxis NICE guideline. However, there are some areas for improvement. It was observed that in cases where an anaphylaxis discharge checklist document was used the department was more compliant with the guidelines. Emphasis on departmental education and providing a checklist to be filled in with every adrenaline autoinjector being prescribed may improve guideline adherence.